Visual literacy and gender sensitivity: teaching art from a feminist perspective. Issue 3 (2nd October 2021) - Scheflan-Katzav, Hadara
Abstract: The premise of the article is that the history of Western art as taught in most art curricula is fundamentally biased and patriarchal. It was primarily feminist scholars who demonstrated how modernist art paradigms are constructed by gender differences and thus reflect and reinforce gender power relations. My claim is that changing the power relations requires visual literacy skills and a new reading that will broaden or modify the standard visual reading of modernist artworks. The study offers a critical visual reading of two foundational artistic themes, each to be read through dialog between the work of a male artist and that of a female artist, the themes being 'girl before a mirror' and 'the origin of the world'. The cases are taken from a course I teach to undergraduate students in education and art. For each of the themes, I present the development of an alternative critical reading of the artworks. I show how the acquisition of skills in critical feminist visual reading helps to promote the deconstruction of traditional gendered representations and allows students to read the woman as a subject rather than an object.